Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense—23. Odontocheila parafemoralis sp. nov., a new species of the O. cajennensis species-complex (Coleoptera: Cicindelidae) - Moravec, Jiří (Zootaxa, 2021)
A new species of the genus Odontocheila Laporte de Castelnau, 1834 is described from Brazil as Odontocheila parafemoralis sp. nov. Along with other species previously treated as subspecies of O. cajennensis (Fabricius, 1787), the new species is classified here as a species of the O. cajennensis species-complex (within the O. cajennensis species-group). It was commonly confused in collections with O. bipunctata (Fabricius, 1792) and O. femoralis Chaudoir, 1860. Specimens from Itaituba, Rio Tapajoz, Pará (the type locality of the new species) were previously considered by the present author to be aberrant adults of O. oseryi (Lucas, 1857) and were also included within the species in the taxonomic revision of the genus (Moravec 2018). A recent examination of numerous specimens from Itaituba has revealed that they represent an undescribed species, which is diagnostically separated from all taxa of the O. cajennensis species-complex. Consequently, it is described here as new to science. Illustrations of the habitus, diagnostic characters and variability of the new species and distinguishing characters of similar species are presented in colour photographs. A revised key to species of the O. cajennensis species-complex (within the complete O. cajennensis species-group) is presented with reference to the taxonomic revision of the genus (Moravec 2018). An essential map of distribution is also given.